2019
DOI: 10.3389/fncir.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bottom-Up and Top-Down Cortical Interactions in Adaptation to Natural Scene Statistics

Abstract: Adaptation is a mechanism by which cortical neurons adjust their responses according to recently viewed stimuli. Visual information is processed in a circuit formed by feedforward (FF) and feedback (FB) synaptic connections of neurons in different cortical layers. Here, the functional role of FF-FB streams and their synaptic dynamics in adaptation to natural stimuli is assessed in psychophysics and neural model. We propose a cortical model which predicts psychophysically observed motion adaptation aftereffects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 89 publications
(137 reference statements)
1
10
0
Order By: Relevance
“…At the same time, the altered motion direction statistics of the natural image sequences can influence the perceived skew after adaptation. Both types of aftereffects, change of perceived skew as well as motion direction, are known to occur for skew distorted natural stimuli (Habtegiorgis et al, 2017(Habtegiorgis et al, , 2019. This all suggests that the tested motion aftereffect is a measurement for distortion adaptation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…At the same time, the altered motion direction statistics of the natural image sequences can influence the perceived skew after adaptation. Both types of aftereffects, change of perceived skew as well as motion direction, are known to occur for skew distorted natural stimuli (Habtegiorgis et al, 2017(Habtegiorgis et al, , 2019. This all suggests that the tested motion aftereffect is a measurement for distortion adaptation.…”
Section: Discussionmentioning
confidence: 87%
“…In progressive addition lenses skew distortions are the prominent type of distortion. After adaptation to skew distorted natural stimuli, the perceived level of image skew of a static pattern changes (Habtegiorgis et al, 2017) as well as perceived motion direction of a test stimulus (Habtegiorgis et al, 2019). The first study also showed that during fixation, the aftereffect is transferred to retinal locations without adaptation stimulation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Through the temporal correlation of frames, not only each image but also motion statistics were strongly influenced by the skew. A description of the resulting motion statistics can be found in Habtegiorgis, Jarvers, Rifai, Neumann, and Wahl (2019a ).…”
Section: Experiments 1: Form Adaptation Aftereffects Induced By Distormentioning
confidence: 99%
“…The materials and methods used in this experiment were the same as in Experiment 1 , except for modifications described below. Motion content of the adaptation stimulus has been thoroughly described in Habtegiorgis et al (2019a ).…”
Section: Experiments 2: Motion Adaptation Aftereffects Induced By Distmentioning
confidence: 99%